CHALLENGES IN INTEGRATING DIGITAL LITERACY IN ELEMENTARY EDUCATION : A QUALITATIVE STUDY - Niken Dwi Lestari, Niken Dwi Lestari; Ayu Dwi Astuti, Ayu Dwi Astuti; Anggi Putri Oktavia, Anggi Putri Oktavia; Vania Belinda Ines Nabilah, Vania Belinda Ines Nabilah; Ari Nur Fadilah, Ari Nur Fadilah; Atmojo, Setyo Eko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Peradaban, 2026)
This study aims to explore the challenges in integrating digital literacy in elementary education at SDN Jaban. The research uses a qualitative approach with a phenomenological design to understand teachers' experiences in implementing digital literacy in the classroom. Data were collected through semi-structured interviews involving five teachers. The findings indicate several main challenges, including limited technological infrastructure, differences in teachers' digital competence, and the absence of structured digital literacy materials. Despite these limitations, teachers show adaptive efforts by utilizing simple digital media such as videos and online quizzes, as well as collaborating with fellow teachers. The results of thematic analysis reveal that teachers are in a transitional phase toward digital learning and require institutional support in the form of training and facilities. This study suggests the need for structured programs and continuous professional development to support effective digital literacy integration in elementary schools